Seasonal Contrast in Precipitation Mechanisms over Nepal Deduced from Relationship with the Large-Scale Climate Patterns - Sigdel, Madan; Ikeda, Motoyoshi (Nepal Journal of Science and Technology, 2013)
Summer precipitation dominates over winter one for the annual total in south Asia, while the winter condition is still important for agricultural productions. Rain gauge data over Nepal were analyzed with large-scale atmospheric patterns such as El Niño-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). In the period of June to September, summer monsoon rainfall over Nepal (SMRN) is generally higher in the eastern region along with a peak in the central region associated with the local orography. Its interannual variability was found to be correlated with the southern oscillation index (SOI): i.e., when La Niña occurs, eastward moisture flux is blocked over Bay of Bengal (BOB) by the anomalous Walker circulation extending from the Pacific. The local-scale condition for higher SMRN is implied by a main moisture route along the eastern arm of the low pressure in northeastern India, as proved by a significant correlation between SMRN and the northward moisture flux. In winter (DJFM), precipitation occurs more in the western region. The higher winter precipitation over Nepal (WPN) was correlated almost equally with positive Dipole Mode Index (DMI) over the Indian Ocean and also SOI, while the relationship with SOI is reversed from summer. A clear linkage was suggested with moisture flux from the Arabian Sea and the further western region. Thus, possible impacts of anomalous precipitation have to be predicted under the relationship with the large-scale indices depending on seasons. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 115-123 DOI: http://dx.doi.org/10.3126/njst.v13i1.7450